A educação a distância na Igreja Católica na América Latina e no Caribe. Vantagens, desafios e possibilidades na formação de missionários(as) - Lopes, Carlos (Revista eclesiástica brasileira, 2007)
For the educational development of male and female lay missionaries that will perform the mission of the Catholic Church in Latin America and the Caribbean, the authors suggest the Distance Education modality (DE). The DE’s features, its utilization models, its advantages and challenges are transversally marked by the idea that this educational modality must be adequate to fulfill the above-mentioned mission and can be used as a space where the opportunities and knowledge of a “capillary army of missionaries” may be shared. This “army” must also be capable of facing the challenges resulting from the emerging cultures and of making use of the information and communication technologies that are now so familiar to our everyday life, but, on the whole, are still unfamiliar to the pastoral action.